Challenges To Online Education: A Review - Suri, Dr. Chanchal Sachdeva (The journal of contemporary issues in business and government, 2021)
The Pandemic Corona Virus Disease popularly known as COVID-19 has impacted not only the developing countries but the whole world. It has affected each aspect whether it is Education, Economy, Social life, etc. In every sector we are adopting digital technologies. The education sector has also adopted new paradigms for imparting knowledge and skills. It has shifted itself from traditional medium to virtual classrooms. All educational institutions at primary, secondary and college/ university levels are adopting new pedagogies to cater to this situation and keep continuity in providing knowledge to its students. Many research works have been done by researchers to know the challenges of online education system. The present study summarises the challenges faced by students in this virtual classroom environment. The researcher selected 16 papers and articles published in various Journals, Scholarly Articles with the help of Google Scholar.